Activation of the endoplasmic reticulum stress response by the amyloid-beta 1–40 peptide in brain endothelial cells - Fonseca, Ana Catarina R. G. (2013)
Neurovascular dysfunction arising from endothelial cell damage is an early pathogenic event that contributes to the neurodegenerative process occurring in Alzheimer's disease (AD). Since the mechanisms underlying endothelial dysfunction are not fully elucidated, this study was aimed to explore the hypothesis that brain endothelial cell death is induced upon the sustained activation of the endoplasmic reticulum (ER) stress response by amyloid-beta (Aβ) peptide, which deposits in the cerebral vessels in many AD patients and transgenic mice. Incubation of rat brain endothelial cells (RBE4 cell line) with Aβ1–40 increased the levels of several markers of ER stress-induced unfolded protein response (UPR), in a time-dependent manner, and affected the Ca2 + homeostasis due to the release of Ca2 + from this intracellular store. Finally, Aβ1–40 was shown to activate both mitochondria-dependent and -independent apoptotic cell death pathways. Enhanced release of cytochrome c from mitochondria and activation of the downstream caspase-9 were observed in cells treated with Aβ1–40 concomitantly with caspase-12 activation. Furthermore, Aβ1–40 activated the apoptosis effectors' caspase-3 and promoted the translocation of apoptosis-inducing factor (AIF) to the nucleus demonstrating the involvement of caspase-dependent and -independent mechanisms during Aβ-induced endothelial cell death. In conclusion, our data demonstrate that ER stress plays a significant role in Aβ1–40-induced apoptotic cell death in brain endothelial cells suggesting that ER stress-targeted therapeutic strategies might be useful in AD to counteract vascular defects and ultimately neurodegeneration.